2022
DOI: 10.1109/jphot.2022.3221777
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-Printed Patterned Quantum Dots Film for High-Efficiency Displays

Abstract: Due to the effect of solution kinetics and crystallization kinetics of quantum dot (QD) during inkjet printing, the inkjet printing technique is prone to form coffee-ring patterns and in-homogenous films. Pioneering efforts are usually limited to mixed solvent or additive inks, in this paper, we investigated polymer QD films with good uniformity obtained by inkjet printing, in order to control the uniformity of quantum dot films in pixels, the mechanism of action of wettability science on inkjet printing was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…[ 94 ] Similarly, Lin et al demonstrated that N 2 O treatment efficiently modulates the surface energy of the bank structure, leading to the realization of uniform QD patterns. [ 95 ] Lee et al treated the bank structure's surface with CF 4 plasma, effectively cleaning and simultaneously modifying the surface, thereby achieving uniform inkjet‐printed QD films within the bank structure [ 96 ] (Figure 6c).…”
Section: Prevailing Qd Patterning Technologiesmentioning
confidence: 99%
“…[ 94 ] Similarly, Lin et al demonstrated that N 2 O treatment efficiently modulates the surface energy of the bank structure, leading to the realization of uniform QD patterns. [ 95 ] Lee et al treated the bank structure's surface with CF 4 plasma, effectively cleaning and simultaneously modifying the surface, thereby achieving uniform inkjet‐printed QD films within the bank structure [ 96 ] (Figure 6c).…”
Section: Prevailing Qd Patterning Technologiesmentioning
confidence: 99%